Esterification of Microwave Induced Pyrolytic Oil from Sago Bark Waste - Rafeah, Wahi; Syamila Aimi, Yahaya; Lam, Su Shiung; Sharifah Mona, Abd Aziz Abdullah; Zainab, Ngaini (Springer, 2019)
In this study, microwave induced pyrolytic oil from sago bark (SB) was subjected to esterification to improve its properties. Improvement on properties of the pyrolytic oil was performed via esterification with ethanol and the presence of sulfuric acid as a catalyst. The optimum esterification condition was studied using general factorial design. The esterified oil (EO) showed improved properties with pH (4–6), reduced moisture content (2.95–3.45%), density (0.9–1.1 g cm−3), and acid value (39.3–123.4 mg KOH−1 g−1), and maintained the CV (20.2–21.6 MJ kg−1). GC–MS analysis showed that EO was sulphur free, and low in carboxylic acid and oxygenated compounds. The optimal esterification condition with optimum quality of EO was at 65 °C temperature, 60 min reaction time and 1:1 ethanol to oil volume ratio. Results indicated that the EO can be potentially used in robust combustion engines upon properties refinement.